2013
DOI: 10.1071/he13042
|View full text |Cite
|
Sign up to set email alerts
|

Effective recruitment and retention strategies in community health programs

Abstract: This study provides novel insights to a greatly under researched topic in the field of health promotion. There are two key take-home messages from the present study that are applicable to health practitioners as well as developers and deliverers of community health-promotion programs: (1) it is imperative that all community health organisations report on the effectiveness of their recruitment and retention, both successes and failures; and (2) there is a clear need to tailor the recruitment and retention appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…The program’s retention rate was high (77.7%) and compared well with similar community-based programs [26, 37]. However some community-based programs for older adults have reported attrition rates of 50%, suggesting this population may be more prone to attrition [30].…”
Section: Discussionmentioning
confidence: 90%
“…The program’s retention rate was high (77.7%) and compared well with similar community-based programs [26, 37]. However some community-based programs for older adults have reported attrition rates of 50%, suggesting this population may be more prone to attrition [30].…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, an understanding of the target population and the program setting are crucial health promotion competencies that ensure more effective delivery of community health programs. 22 The IMSS has demonstrated that a large proportion of sheds offer a range of diverse health promotion programs, suggesting that shed participants find the setting of Men's Sheds conducive to such activities.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, habilidades sociais do moderador e demais membros da equipe técnica, nível de confiança estabelecida entre partes ao longo do tratamento, e possibilidade de escolhas/decisões dos participantes na execução de tarefas delimitadas (coparticipação e responsabilização pessoal), implicam diretamente, tanto na adesão, quanto na retenção de participantes (Martin, Williams, Haskard & DiMatteo, 2005). Tendo em vista que todos estes aspectos foram cuidadosamente avaliados neste estudo, com devida capacitação prévia de equipe, conforme sugerido para boas práticas em saúde (McCann, Ridgers, Carver, Thornton & Teychenne, 2013;Windosor, 2015), com altos índices de confiabilidade obtidos entre observadores para adesão dos participantes, e habilidades sociais e integridade/fidelidade do moderador, e também a partir de relatos dos próprios participantes (compreensão e generalização dos conteúdos), estes cuidados podem ter influenciado no alto índice de retenção do programa.…”
Section: Discussionunclassified